The influence of transformational leadership practices and Islamic leadership core values on teachers' job satisfaction - Saidova, Parvina (Kulliyyah of Education, International Islamic University Malaysia, 2018)
Malaysian Government launched the Malaysia Education Blueprint in 2013 to outline the course of education transformation over the next period and to respond to many of the challenges encountered by the system. Although the application of transformational leadership in schools was a subject of investigation for decades, still the theory and practice of the role of transformational leadership remains to be an important issue. Hence, the main purpose of this study is to investigate the validity of the proposed practices of transformational leadership in Malaysian secondary schools from school leaders' and teachers' perspectives. The precise objectives were to estimate the model, to measure the influence of transformational leadership practices on teachers' job satisfaction and its relationship with Islamic Leadership core values. Seven hundred (N=700) questionnaires were administered to teachers and school leaders from four types of secondary schools (SMK; SMKA; SMS and MRSM) in Selangor, Malaysia. Out of the total questionnaires distributed (N=700), only 547 questionnaires were collected. Structural Equation Modeling (SEM) and Confirmatory Factor Analysis (CFA) are used to examine the direct effects of transformational leadership practices and Islamic leadership core values on teacher's job satisfaction. Structural equation modeling hypothesis-testing procedures indicated an acceptable fit revealing that the practice of transformational leadership such as setting direction, helping people and redisigning the organization has an effect on teachers' job satisfaction. The causal relationship is relatively high with standardized direct effect of 0.410 (CR >1.96). Also, Islamic leadership core values significantly influenced teachers' job satisfaction with staderdized direct effect of 0.599 (CR>1.96). The estimation indicates that the practice and belief of Islamic leadership such as tawhid, khalifah, amanah and adalah by teachers themselves contribute immensely to their job satisfaction. Transformational leadership practices has a significant relationship with Islamic leadership core values with standardized correlational effect of 0.556. The current study explored how this style of leadership contributes in upholding the teachers' trustworthiness on their school leaders and proposed a model. The statistical findings were corresponding with research objectives and the research questions were answered with respect to statistical validations portraying with AMOS graphic.